Wizja, odwaga, realizacja – aplikacje libsmart w Bibliotece Uniwersyteckiej w Poznaniu - Karwasiński, Piotr; Gniot, Aleksander (My University, 2013)
Are electronic library services frightening, and if so, do they scare librarians or readers more? How to design innovations “with a vision” in the era of developing information technology and how to carry out the process of their implementation? The authors involved in the process of designing, launching and administrating the pioneering LIBSMART package applications want to prove that the virtual library is in fact a real library, digital media distribute the same content as the print book, and e-services are a means of bringing the reader and the library closer. The speech will go through the main ideas of innovations provided by the Poznań University Library (electronic payment, virtual communication platform, integrated system of remote ordering of copies, electronic reminders and notices), changes in the work organization under the influence of their implementation, new areas of librarians’ interests during the implementation of the project and the difficulties they had to face and overcome in order to achieve the desired result – user satisfaction. During the presentation, its authors will outline an optimal model of computer systems for the XXI century library.
Jest to wersja artykułu po recenzji. Artykuł ukaże się w publikacji z międzynarodowej konferencji Biblioteki Uniwersytetu Łódzkiego 4-6.06.2013 r. "Biblioteka w komórce? przyszłość usług bibliotecznych".
Keywords: informatyzacja; usługi elektroniczne; libsmart; biblioteka elektroniczna; biblioteka wirtualna; e-usługi